Progression and Treatment Cost of Patients with Chronic Kidney Disease - Martwanna, Woranot; Boonjarat, Sirirat; Suvannakud, Pensri; Juntava, Daungnapa (Journal of Health Science of Thailand, 2017)
This study was a retrospective cohort study using data extracted from electronic medical records in Khueang Nai Hospital, Ubon Ratchathani. Participants were patients diagnosed with chronic kidney disease (CKD)between 1 October 2006 and 30 September 2011. Patients who hadglomerular filtration rate (GFR) less than 60 ml/min/1.73 m2 in two separate serum creatinine were included. GFR was estimated using the Modification of Diet in Renal Disease (MDRD). The objective of this study was to determine the progression and treatment costs in CKD patient. Kaplan-Meier plots and generalized linear models were used for analyses. There were 2,336 patients, 59.5 percent were female and mean age was 73.9, (10.9) years. At the end of a three-year follow up, 30 percent of CKD stage 3 patients developed stage 4 and 38 percent of stage 4 patients developed stage 5. Cost of treatment in fiscal year 2007 were 1,412 Baht per patient-year and increasing to 2,390 Baht per patient-year in fiscal year 2011. The cost increased gradually 18 percent per year.Drug cost was the main proportion of treatment cost. Factors that seemed to be associated with treatment cost were male has 2.47 times higher cost of treatment than that of female (p 0.001), diabetes patients had 8.76 times higher cost of treatment than non diabetes patients (p<0.001) and CKD stage 4 has 4.27 times higher cost of treatment than CKD stage 3 (p<0.001). In conclusion, this study indicates that disease progression was still rapid and hence impacted on cost of treatment. Further implementations on intervention aiming to slow the progression of patients with CKD should be conducted.